PLAY, LEARN, AND SPEAK: A NARRATIVE INQUIRY INTO GAMIFIED ENGLISH LEARNING AMONG ADOLESCENTSPLAY, LEARN, AND SPEAK: A NARRATIVE INQUIRY INTO GAMIFIED ENGLISH LEARNING AMONG ADOLESCENTS - Aida Fitrianah Zen (JETS: Journal of English Teaching Strategies, 2024)
This study explores how Indonesian adolescents use gamified environments such as Duolingo, Roblox, Minecraft, Memrise, and Kahoot to develop their English speaking skills. Employing a narrative inquiry method, it examines the learners’ experiences, focusing on how digital games contribute to motivation, confidence, and linguistic competence. Participants shared how platforms like Roblox and Minecraft facilitated real-time interaction in English, enhancing fluency and vocabulary. The findings highlight the educational potential of these tools in informal learning contexts and contribute to the broader conversation on digital innovation in language education. Future researchers are encouraged to adopt mixed-method or longitudinal designs to provide deeper insights into causal relationships and track language development over time in diverse educational settings.